KONFLIK SOSIAL TERHADAP PERBEDAAN PENDAPAT RUKYATUL HILAL DALAM MENENTUKAN KALENDER ISLAM - Sari, Putri Waliyu; Amir, Rahma (Universitas Islam Negeri Alauddin Makassar, 2026)
ABSTRACT This relselalrch discusses social conflict regarding differences of opinion on rukyatul hilal in determining the Islamic calendar. The formulation of the problem in this thesis is firstly, namely, what is the method for determining the Islamic calendar, secondly what is the social conflict that occurs due to differences of opinion on rukyatul hilal in determining the Islamic calendar, thirdly what is the solution to responding to differences of opinion on rukyatul hilal in determining the Islamic calendar. This research uses heritage research (Library Research) in looking for articles, theses, journals and books that are related to the author's title. The approaches used by the author are the Sharia approach and the astronomical approach. According to the data source, the data in this research is divided into two data, namely primary data and secondary data. The results of this research show that. Firstly, the methods used to determine the Islamic calendar are Rukyatul Hilal (bil fi'il), Wujudul Hilal (ijtima'qobla qurub), Imkanur rukyat MABIMS and Global Rukyat (matla-al badar). Second, the social conflict that occurs is that there are differences of opinion in determining the Islamic calendar, especially regarding the method between reckoning and rukyat, which can cause significant social conflict. This conflict arises from various factors, including differences in criteria which still adhere to the opinions of schools of thought and hisab or rukyat experts. Third, the solution in responding to differences of opinion on rukyatul hilal in determining the Islamic calendar is to eliminate the principle that one method between groups is the most effective, reaching agreement on the methods and criteria applied. Convey information through seminars and training in Astrology and the government-MUI becomes an intermediary with the hisab and rukyah groups for valid decisions. The implication of this research is that research shows that there are several methods used to organize the Islamic calendar. This highlights the need for a deeper understanding of these various methods and their application to religious practice. This researcher hopes that with this research, it can increase scientific insight regarding Falak Science, especially regarding differences of opinion on rukyatul hilal in determining the Islamic calendar. And it is hoped that groups or mass organizations will hold deliberations or seminars on Falak Science to find solutions to differences of opinion in determining the Islamic calendar.